Risk factors identified in prenatal child protection reports. (March 2021) - Meiksans, Jenna; Arney, Fiona; Flaherty, Rosemaria; Octoman, Olivia; Chong, Alwin; Ward, Fiona; Taylor, Cathy
Highlights: Risk factors were identified from the narratives of prenatal child protection reports. Most families were reported to be experiencing three or more risk factors. Prenatal supports must address multiple co-occurring problems. Abstract: The prevalence of prenatal reporting to child protection is estimated to be 3% of Australian pregnancies. Understanding risk factors associated with prenatal child protection involvement is critical in identifying the needs of families who may benefit from early intervention. This paper reports findings of a case file review examining characteristics of families reported prenatally. Unit-record administrative data were extracted for unborn children reported to child protection in a single Australian jurisdiction during 2014. Intake reports relating to a 20% random sample (n = 131 unborn children) were coded using a tailored coding guide developed for this study. Most families were reported to be experiencing three or more risk factors, including current or previous intimate partner violence (70% of families), parental alcohol and other drug use (63%), parental mental health concerns (58%) or parent criminal activity (34%). Over one-third of parents in the sample had themselves experienced abuse and neglect as children. In families with more than one child, more than 90% of older siblings of unborn children had been the subject of a previous report. Supports must address multiple co-occurring problems, often in the context of personal and familial histories of child abuse and neglect, meaning that risks are intergenerational and enduring.